The New Audiobook Industry: Digitizing Reading through Hearing - Razani, Nabilah; Via Lesmana (EKSPRESI DAN PERSEPSI : JURNAL ILMU KOMUNIKASI, 2024)
Technological developments have changed how people communicate and read, especially audiobooks. Initially, audiobooks were aimed at helping people with special needs and reading difficulties. However, with digitalization, audiobooks are becoming a more popular format and have platforms with subscription services. This research aims to explore recent developments in the audiobook industry and re-evaluate the concept of reading by ear in the digital era. This research uses a literature review method by collecting and analyzing various library sources relevant to audiobooks. The audiobook industry is experiencing rapid growth as digital audiobooks become increasingly popular. Audiobooks are an alternative to printed books and an independent medium that offers a different reading experience. Audiobooks have also been shown to improve general literacy skills, positively impact older people's mental health, and improve sleep quality and meaning. The development of the audiobook industry has revolutionized how humans consume literary content, opening a new window into the world of stories and knowledge through hearing. The development of the audiobook industry influences how people read literature by making access more accessible, increasing engagement, and enriching the reader's experience. This shows the importance of adapting to technology in forming new ways of reading and listening to literary works. Audiobooks also have a role in various aspects of human life, such as education, literature, entertainment, and health.